Uji Kualitatif Merkuri pada Krim Pemutih Wajah yang Tidak Terdaftar Badan Pengawas Obat dan Makanan di Kabupaten Tulungagung - Andyanita Hanif Hermawati; Qurrotu A’yunin Lathifah (Borneo Journal of Medical Laboratory Technology, 2019)
The cream used to brighten up the skin and fades freckles of the face is called whitening cream. Mercury is the active ingredient that is commonly used in face whitening cream. The use of hazardous substances in cosmetics namely mercury. Irritation, nervous disorders, itching, until skin cancers are the result of the use of mercury in whitening cream. This research aims to find out whether there is mercury or not by qualitative test in whitening cream which is unregistered by Badan Pengawas Obat dan Makanan (BPOM) in Tulungagung. The type of this research is descriptive research. The number of whitening cream samples which is unregistered by Badan Pengawas Obat dan Makanan (BPOM) Tulungagung as many as six samples. Colour test used 0.5 N KI solution is a qualitative test of mercury. Results of the study with a qualitative analysis show that all negative samples contain mercury.